A Fast and Accurate Method for the Quantification of Doxycycline in Goat Plasma and Milk by HPLC Using a Fluorescence Detector - Martínez José; Hernandis Verónica; Badillo Elena; Escudero Elisa; Yuste María Teresa; Galecio Juan Sebastián; Marín Pedro (Acta Veterinaria)
Doxycycline is an antimicrobial agent used in veterinary medicine to treat a variety of bacterial infections. To date, no analytical technique utilising HPLC with fluorescence detection has been documented for the quantification of doxycycline concentrations in goat plasma or milk. Consequently, the objective of the present study was to propose a rapid HPLC assay with fluorescence detection for the quantification of doxycycline in the aforementioned samples, thereby facilitating the conduct of pharmacokinetic studies and the detection of residues in diverse goat tissues. Proteins were precipitated with methanol and trifluoroacetic acid in a single step. Doxycycline was separated on a XBRIDGE C18 column using an isocratic method. Sample volume injected into the HPLC system was 50 µl. Fluorescence detection was conducted with an excitation wavelength of 380 nm and an emission wavelength of 520 nm. The retention times of doxycycline and danofloxacin (internal standard) were determined to be 8.0 and 5.5 minutes, respectively. The calibration curves for plasma and milk exhibited linearity over the concentration range of 0.1 to 2 μg/mL. The limit of detection was 0.065 μg/ mL, while the limit of quantification was 0.1 μg/mL in both matrices. The accuracy and precision of the method were consistently within the limits of 10.9% for plasma and 10.5% for milk. The findings of this study may be employed in the quantification of doxycycline in goat plasma and milk, thus facilitating the conduct of pharmacokinetic studies.